Pengabdian Masyarakat Desa Semboro Melalui Mitigasi Banjir Berbasis Rasio Hazard dan Vulnerability - Luluk, Hadiqotul; Prasetyohadi, Dio Catur; Jannah, Miftahul; Marline, Naresha; Aldilla, Anggita Septi; Herminingsih, Hesti (Dedication : Jurnal Pengabdian Masyarakat, 2026)
Flooding is a frequent environmental problem in RW 025, Semboro Village, Jember Regency, due to high rainfall and low soil absorption capacity. This community service activity aims to improve the community's ability to mitigate flooding through a hazard and vulnerability ratio-based approach, including the application of biopore technology and environmental restoration. The method used was descriptive qualitative, through field observation, interviews, documentation, and community mentoring. The activity included site surveys, the installation of 40 biopore infiltration holes, riverbank cleaning, vegetation planting, and activity evaluation. The results of the community service program demonstrated increased community understanding and participation in environmental management, a reduction in the potential for flooding at vulnerable points, and the formation of a follow-up team to maintain the sustainability of the flood mitigation program. This activity is expected to support efforts to reduce the risk of inundation on a sustainable basis at the village level.